(untitled) (International Journal of Nursing Education, 2022)
Various media on hand hygiene topics have been developed to make it easier for students to master the procedure, but positive attitudes toward applying these skills have not significantly developed. The study aimed to determine the effect of hand hygiene history on undergraduate nursing students’ attitudes to hand hygiene. A quasi-experiment using a pre-and post-test with a control group design was conducted. Fifty-four students were invited and randomly assigned to an intervention group and a control group. The intervention group obtained the hand hygiene history through a booklet, while the control group got no treatment. The data were collected using a questionnaire. The paired and unpaired t-test was applied to analyze the data. The results showed that the average score of students’ attitudes in the intervention group increased from 58.44±5.98 to 65.52±5.29 (p<0.001), while in the control group, it only increased from 60.41 ± 4.12 to 60.78 ± 5.06 (p=0.769). There was a significant difference in the attitude value between the two groups (p = 0.021). In conclusion, hand hygiene history improved students’ attitudes toward hand hygiene significantly. This study recommends complementing hand hygiene learning with its history so that students are skilled and have the expected attitude to apply it.